Airborne contamination during post-fire investigations: Hot, warm and cold scenes. Issue 1 (2nd January 2022) - Horn, Gavin P.; Madrzykowski, Daniel; Neumann, Danielle L.; Mayer, Alexander C.; Fent, Kenneth W.
Abstract: Fire investigators may be occupationally exposed to many of the same compounds as the more widely studied fire suppression members of the fire service but are often tasked with working in a given exposure for longer periods ranging from hours to multiple days and may do so with limited personal protective equipment. In this study, we characterize the area air concentrations of contaminants during post-fire investigation of controlled residential fires with furnishings common to current bedroom, kitchen and living room fires in the United States. Area air sampling was conducted during different investigation phases including when investigations might be conducted immediately after fire suppression and extended out to 5 days after the fire. Airborne particulate over a wide range of dimensions, including sub-micron particles, were elevated to potentially unhealthy levels (based on air quality index) when averaged over a 60 min investigation period shortly after fire suppression with median PM2.5 levels over 100 µg/m 3 (range 16–498 µg/m 3 ) and median peak transient concentrations of 1, 090 µg/m 3 (range 200–23, 700 µg/m 3 ) during drywall removal or shoveling activities. Additionally, airborne aldehyde concentrations were elevated compared to volatile organic compounds with peak values of formaldehyde exceeding NIOSH ceiling limits during the earliest investigation periods (median 356 µg/m 3, range: 140–775 µg/m 3 ) and occasionally 1 day post-fire when the structure was boarded up before subsequent investigation activities. These results highlight the need to protect investigators' airways from particulates when fire investigation activities are conducted as well as during post-fire reconstruction activities. Additionally, vapor protection from formaldehyde should be strongly considered at least through investigations occurring 3 days after the fire and personal formaldehyde air monitoring is recommended during investigations.